Irrigação por gotejamento: I — Características hidráulicas do microgotejador irtec - Alves de Faria, Manoel; Bernardo, Salassier; Ferreira, Paulo Afonso; Torres Loureiro, Blanor (Revista Ceres, 2025)
At the Hydraulics Laboratory of the Federal University of Vicosa, Viçosa, Minas Gerais, Brazil, a study was conducted to determine hydraulic characteristics of the micro-drip IRTEC. The drip was submited to three types of tests: one with temperature and pressure constant; one with constant temperature and variable pressure; one with constant pressure and variable temperature. It was found that the micro-drip IRTEC was not affected by the variation of temperature from 20 to 45°C nor by the variation of pressure from 5 to 25 m.c.a.